Water catchment area and management method - Ibrahim Abdullah Abu Ala, Alfituri; A. Amhimmid Alqantosh, Aisha; Ahmed Dhafer Ahmed, Kandash; Abdul Hamid, Nur Jannah; Mohd Noor, Khairiyah (Penerbit UTHM, 2020)
Due to critical and obvious effect of the wastewater comes from the industry, agriculture and industrial activity nearby the dam has led to environmental issues in Sembrong dam, Kluang Johor which caused negative impacts to the biological, chemical and physical properties of water river environments. The dam itself contained a large number of algae which caused the blocking of sunlight, could not enter directly to the water surface and it threatening to the aquatic life. The dam also traps sediments, which are crucial for maintaining physical progressions and habitats of the dam. The chapter introduce “G.E.T” formula as management method to overcome the pollution problems. The implementation of “G.E.T” formula is basically to improve the urban environmental condition as key for urban policy and environmental management. Sustainable management and utilisation of resources is a guidance in pursuing the development of agricultural and forestry activity at dam area.